Effectiveness of Drip Irrigation with Mineralized Drainage Water for Cotton Cultivation (Multidisciplinary Journal of Science and Technology, 2025)
The articlepresents theresults ofgrowing cottonundertheconditions ofsalinemeadow–alluvial soilsin the Bukhara region, where the groundwater level is 2.0 - 2.5 m, using mineralized water for dripirrigation. When the pre-irrigation soil moisture was maintained at 70 – 80 - 65% of the field capacity,cotton was irrigated 15 times according to the 3 - 10 - 2 scheme. The crop was not irrigated duringthe period from germination to flowering, while during the flowering and boll formation stages,irrigation norms ranged from 273 to 437 m³/ha, with a total seasonal irrigation rate of 4483 m³/ha.Asa result, compared to the control variant, water savings of 1594 m³/ha were achieved.